Students' perceptions on the quality of services delivered by educational administrators at the Institute of Education (INSTED), IIUM - Ibn Usman, Muhammad Awwal (Institute of Education, International Islamic University Malaysia, 2010)
The quest for service quality has been advocated in various instances by many scholars in the present information age where service quality delivery is seen as an important tool for competitive advantage in an institution or organization. Therefore this study is an attempt to examine the students' perceptions on quality of services delivered at Institute of Education, IIUM. A total of 219 respondents were used in the study and each respondent is requested to indicate his experience and perceptions on the service quality using the SERVPERF instrument. In addition the validity and reliability of the instrument used were established using the Cronbach's alpha coefficient and Pearson correlation coefficient for proper items loading. The findings indicated that the overall service quality was perceived positively and Tangible is the most present service quality dimension at INSTED. Also, it is found that the age of respondents strongly influence their perceptions on service quality while no significant difference occur regarding gender, nationality, study level and working experience of the respondents. Implications and Recommendations for future improvement of service quality delivery and practice were channeled to the appropriate authorities.